Italian Coronacrisis and its Repercussions: National, European, and Global Dimensions - E. A. Maslova (Международная аналитика, 2020)
In early 2020, humanity has confronted with a pandemic challenge. The new coronavirus as an international threat has forced states to recognize that they cannot fulfill their principal constitutional obligation - to ensure the safety of their citizens. Coronavirus, as a global threat, despite its pre-industrial nature, is, in all respects, a distinctive challenge of postmodern society. The danger of coronavirus manifests itself non-linearly in time and space – first appeared in China, the virus flared up in other parts of the world, including the Apennines. In Europe, Italy has become an anti-leader in terms of the number of infected and victims. With scientists arguing about the causes of the outbreak of the virus on the Apennines, the null patient is yet to be found. However, the same reason gives rise to different consequences. For Italy, the pandemic had an impact on both national and foreign policies, including relations with the EU, Russia and China. The purpose of this article is to analyze the implications of the coronavirus pandemic for the Italian Republic at different levels – national, pan-European, and global.